Pharmacoeconomic analysis of Cellex® in the treatment of ischemic stroke - A. E. Cheberda; D. Yu. Belousov (Izdatelstvo OKI, 2018)
Actuality. Acute cerebral circulation disordersremain an important problem of modern health care. Available evidence suggests that both reperfusion and neuroprotection are important to ensure a favorable outcome of treatment. In the context of neuroprotection, considerable interest are peptideswith neuroprotective properties. A recent randomized controlled trial of the Cellex® showed positive results for treatment of severe patients with acute cerebral circulation disorders with less favorable outcomes and the highest direct medical costs, which makes the question of assessing the pharmacoeconomic properties of this drug relevant in the light of new data. Objective. To conduct a clinical and economic analysis of treatment outcomes for Cellex® and therapeutic alternatives used in patients with Acute cerebral circulation disorders and early rehabilitation period of the disease within the framework of the state guarantee programs of free medical care. Methodology. Pharmacoeconomic modeling, cost-eectiveness analysis, budget impact analysis. Results. Established that the use of Cellex® in the context of Russian practice in patients corresponding to the characteristics of the target population of this pharmacoeconomic study leads to reduce the budget burden by 26 % for 1 year, reaching 46 % at 4 years. e cost-eectiveness analysis indicates that Cellex® leads to greater eciency in the use of health resources. e sensitivity analysis conrms the stability of this result to a change in the market situation, expressed in an increase in the price of Cellex® preparation to 25 % inclusive. This indicates a high pharmacoeconomic feasibility of Cellex® in the context of therapy the ischemic form of acute cerebral circulation disorders in Russian Federation.